2003
DOI: 10.1021/nl034646b
|View full text |Cite
|
Sign up to set email alerts
|

Silica Nanoarchitectures Incorporating Self-Organized Protein Superstructures with Gas-Phase Bioactivity

Abstract: We have encapsulated self-organized protein superstructures containing cytochrome c into a mesoporous silica-based nanoarchitecture. The protein superstructure, nucleated by colloidal gold in buffered medium and nanoglued with silica sol, remains intact upon supercritical drying of the wet composite gel and exhibits rapid gas-phase recognition of NO. We posit that specific adsorption of the heme edge at nanoparticulate Au creates a high radius-of-curvature nanoscale hybrid that induces protein−protein self-dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
114
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 23 publications
1
114
1
2
Order By: Relevance
“…High overall porosity, good accessibility of pores, high active surface area and possibility to maintain a variety of materials make silica aerogels a potential matrix for the design of biological sensor [197] [245,246]. Ayers et al [196] in their pioneering work, utilized photoluminescence silica-based aerogel as an active element Power et al [65] reported biosensor based on wetted mesoporous silica aerogels, which can be integrated as a scaffold for immobilization and growth of bacteria with a special biological function of their porosity for detection and collection of aerosol viral particles.…”
Section: Aerogel For Biosensing Applicationsmentioning
confidence: 99%
“…High overall porosity, good accessibility of pores, high active surface area and possibility to maintain a variety of materials make silica aerogels a potential matrix for the design of biological sensor [197] [245,246]. Ayers et al [196] in their pioneering work, utilized photoluminescence silica-based aerogel as an active element Power et al [65] reported biosensor based on wetted mesoporous silica aerogels, which can be integrated as a scaffold for immobilization and growth of bacteria with a special biological function of their porosity for detection and collection of aerosol viral particles.…”
Section: Aerogel For Biosensing Applicationsmentioning
confidence: 99%
“…This work showed that the defect density of SAMs on the gold substrates created from NP films can have a significant impact in how those SAMs can be used or how they perform in a specific application like protein monolayer electrochemistry where it can impact the signal-to-background of the voltammetry. By better understanding the properties of SAMs that form on the NP-based gold, one can begin to engineer these methods for application to three-dimensional or porous materials applications [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…It appears that in these hydrophobic organically modified gels (so-called ambigels) the unfavorable [174] contraction observed during the drying and conversion from hydrogel to xerogel is strongly decreased or even suppressed, the xerogel being generally preferred in regard to mechanical properties and chemical resistance. Note that to avoid the drawback of drying, aerogel obtained after supercritical drying can be used to entrap enzymes [175][176][177] and even self-organized protein superstructures [178].…”
Section: Immobilization In Siomentioning
confidence: 99%